Review of Jan Carson's Poetics of Care, by Vanessa Boullet, Nathalie Collé, Monica Latham, Doriane Nemes and Pauline Schwaller - Marie Gemrichová (Review of Irish Studies in Europe)
Review of Jan Carson's Poetics of Care, by Vanessa Boullet, Nathalie Collé, Monica Latham, Doriane Nemes and Pauline Schwaller (Nancy: Éditions de l’Université de Lorraine, 2024), 290pp., ISBN: 978-2-38451-065-5, €25